Distribution, Damage Severity and Management of Dacine Fruit Flies in Nepal: A Review - Sapkota, Rekha; Thapa, Resham Bahadur; KC, Gopal Bahadur; Bajracharya, Ajaya Shree Ratna; Sharma, Moha Datta; Dahal, Kishor Chandra (Nepalese Horticulture, 2024)
Fruit flies are economically significant pests in horticultural crops. The diversity of dacine fruit fly species (Family: Tephritidae; Sub-family: Dacinae; Tribe: Dacini) varies depending on location, season, crop, and variety. This review explores various aspects of fruit fly management in fruits and vegetables, including their distribution across regions, districts and crops with reference to published articles, theses, proceedings and reports in Nepal. The most commonly reported genera in Nepal are Bactrocera, Zeugodacus, and Dacus. Z. cucurbitae (Coq.) and Z. tau (Walker) are reported major pests in cucurbits, while B. minax (Enderlein) reported in sweet oranges. Across these three genera, 28 fruit fly species have been reported in 31 districts (27 in the hills and 4 in the Terai). Seventeen species were reported in Kaski district, while more than 10 species reported in Chitwan, Nawalparasi, Sindhuli, Tanahun, and Kathmandu. Average damage to cucurbit crops ranged from 26-51%, with a maximum of 74% damage reported in sweet oranges. Due to the oligophagous and polyphagous nature of these species, controlling them with a localized management method is challenging in Nepal, where farmers cultivate multiple crops. Integrated management practices, including cultural, botanical, chemical pesticides, and cue-lure traps, are recommended for cucurbits, while a community-level area-wide control program is advised for sweet orange orchards.